ARTYKUŁ PRZEGLĄDOWY/REVIEW PAPERThe modern diagnostics of Sjögren syndrome - Prajs, Krzysztof; Brzosko, Marek; Fischer, Katarzyna; Walecka, Anna; Chosia, Maria; Maj, Piotr (Reumatologia/Rheumatology, 2005)
Sjögren\'s syndrome is considered to be a chronic systemic exocrinopathy of unclear origin, characterized by lymphoid cells infiltration in tissue of exocrine glands resulting in their partial dysfunction or fatal failure. Commonly inflamatory process affects salivary and lacrimal glands. To diagnose the Sjögren\'s syndrome the good known and acknowlegded methods are used, according to American-European Consensus Group criterias. Modern methods such as: ultrasonography, magnetic resonance imaging and magnetic resonance sialography of salivary glands, anti-alfa-fodrin antibodies, autoantibodies against M 3 muscarinic acetylcholine receptor are used so as to definitively settle the diagnosis. So far as the radiological examinations seems to be included soon in obligatory diagnostic methods so the value and utility of new serological markers is ambiguous.